Mental Workload Analysis of Student Members of the Mosque Management Committee at Campus X Using NASA-TLX - Alfani, Musaddad; Wicaksono, Mahruri Arif; Syafnijal, Frieska Ariesta; Qalbi, Putri Aysha (UNIPA PRESS, 2026)
Students who serve as administrators of campus mosques often face dual responsibilities: fulfilling academic obligations while simultaneously managing various religious activities on campus. Balancing these roles can lead to a considerable mental workload. This study aims to assess the level of mental burden experienced by students actively involved as campus mosque administrators. The research was conducted at a university mosque located in Yogyakarta. Mental workload was measured using the NASA-TLX instrument, which evaluates six key dimensions of cognitive load. Findings revealed an average mental workload score of 71.14, categorized as high. A total of 80% of participants reported experiencing high to very high levels of mental stress. The most prominent contributing dimensions were mental demand, effort, and perceived performance. These results highlight the need for effective workload management strategies, including equitable task distribution, engagement of external volunteers, stress and time management training, and promoting awareness of the importance of balancing academic and organizational commitments.